Chemical climatology of atmospheric pollutants in the eastern United States: Seasonal/diurnal cycles and contrast under clear/cloudy conditions for remote sensing. (1st June 2019) - He, Hao; Vinnikov, Konstantin Y.; Krotkov, Nickolay A.; Edgerton, Eric S.; Schwab, James J.; Dickerson, Russell R.
Abstract: We statistically assessed temporal variations of observed concentrations of eight atmospheric pollutants (SO2, NO, NO2, NOy, O3, CO, NH3, and HNO3 ) at three urban sites and one rural site in the eastern United States for a ten-year period (4 years for NH3 ). Diurnal/seasonal patterns of observed mean concentrations and their decade-scale trends under different weather conditions were evaluated. Concentrations of pollutants decreased consistently during the observation period (as long as 1997–2013), although nighttime ozone during winter appears to increase because of reduced NO-O3 titration. This study shows that the decay time of major air pollutant concentrations such as SO2 and NOx can be short as a few hours to one day. We also identified substantial differences between the mean concentrations of pollutants at clear sky and overcast conditions that could introduce biases into satellite observations. Surface concentrations of SO2 and CO are distinctly higher under cloud free than under overcast conditions by ∼30% and ∼20% respectively. NO2 shows a complex pattern, but demonstrates lower daytime concentrations under cloud-free skies. All of these estimates are important for understanding the chemical climatology of these atmospheric pollutants, especially their diurnal/seasonal cycles under different weather conditions. For four-year measurements, NH3 shows a substantial difference, with clear-sky observations roughly a factor of two higher than those under overcast conditions. To track changes in the future, the full daily cycle of atmospheric pollutants monitored by geostationary satellite such as the future TEMPO mission may better capture patterns and trends. Highlights: Long-term record of pollutants in the eastern U.S. was used to construct climatology. Diurnal/seasonal cycles and trends in pollution show the effectiveness of regulations. Nighttime ozone in winter increases due to reduced NO-O3 titration in past decades. Differences in pollutant levels are found under clear sky and overcast conditions.